Homelands the history of a friendship - Ramaswamy, Chitra 1979- (Canongate, 2022)
" A book about history, friendship, family and what it means to belong, from the award-winning journalist and author of Expecting.This book is about two unlikely friends. One born in 1970s Britain to Indian immigrant parents, the other arrived from Nazi Germany in 1939, fleeing persecution. This book is about common ground. It is a story of migration, anti-Semitism, racism, family, belonging, grief and resilience. This book is about the past and the present. It is about the state we're in now and the ways in which we carry our pasts into our futures. This book is about homelands"--Publisher's description
Keywords: Friendship / Great Britain; Children of immigrants / Great Britain; Immigrants / Great Britain; Amitié - Grande-Bretagne; Enfants d'immigrants - Grande-Bretagne; Children of immigrants; Friendship; Immigrants; Biographies; Autobiographies; Great Britain